Increased risk of inflammatory bowel disease in women with endometriosis: a nationwide Danish cohort study. Issue 9 (19th December 2011) - Jess, Tine; Frisch, Morten; Jørgensen, Kristian Tore; Pedersen, Bo Vestergaard; Nielsen, Nete Munk
Abstract : Background: An association between endometriosis and certain autoimmune diseases has been suggested. However, the impact of endometriosis on risk of inflammatory bowel disease (IBD) remains unknown. Objective: To assess the risk of Crohn's disease (CD) and ulcerative colitis (UC) in an unselected nationwide Danish cohort of women with endometriosis. Design: By use of national registers, 37 661 women hospitalised with endometriosis during 1977–2007 were identified. The relative risk of developing IBD after an endometriosis diagnosis was calculated as observed versus expected numbers and presented as standardised incidence ratios (SIRs) with 95% CIs. Results: Women with endometriosis had a increased risk of IBD overall (SIR=1.5; 95% CI 1.4 to 1.7) and of UC (SIR=1.5; 95% CI 1.3 to 1.7) and CD (SIR=1.6; 95% CI 1.3 to 2.0) separately, even 20 years after a diagnosis of endometriosis (UC: SIR=1.5; 95% CI 1.1 to 2.1; CD: SIR=1.8; 95% CI 1.1 to 3.2). Restricting analyses to women with surgically verified endometriosis suggested even stronger associations (UC: SIR=1.8; 95% CI 1.4 to 2.3; CD: SIR=1.7; 95% CI 1.2 to 2.5). Conclusion: The risk of IBD in women with endometriosis was increased even in the long term, hence suggesting a genuine association between the diseases, which may either reflect common immunological features or an impact of endometriosis treatment with oral contraceptives on risk of IBD.